GRAMMATICAL AND TEXTUAL EQUIVALENTS ASSOCIATED WITH TRANSLATIONS STRATEGIES - Agung, Winantu Kurnianingtyas Sri (Jurnal Bahasa Lingua Scientia, 2011)
Translation is not just divert the messages away, but also should pay attention to choice appropriate words to achieve the equivalence, whether grammatically and textually. Since the equivalence itself is closely related to the concept of translatable and untranslatable. Furthermore, each language has its own rules which may be difficult or even cannot be translated into other languages. Therefore, the translator must know the right manners to achieve grammatical and textual equivalence. At this time, this research raised the issues that often encountered by the translator during the translation processing, such as to achieve grammatical and textual equivalence between source language and target language, and some strategies that can be applied by translator to reach that goals.